The Development of Arabic Language Education in the Digital Age: A Systematic Literature Review - Widodo Widodo; Khadiatun Khadiatun; Ahmad Sunoko; Muhammad Jafar Nashir (JURNAL PEDAGOGY, 2026)
This study presents a Systematic Literature Review (SLR) aimed at mapping the development of Arabic language education in the digital era over the past decade (2014–2024). Guided by the PRISMA 2020 protocol (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), this review analyzed 42 peer-reviewed articles selected from an initial pool of 187 studies identified across Google Scholar, ERIC, Scopus, and the national SINTA journal portal. Thematic synthesis revealed four major themes: (1) the integration of digital platforms and mobile applications in Arabic language instruction; (2) the effectiveness of blended learning and e-learning approaches for developing maharah lughawiyah (Arabic language skills); (3) the design and validation of gamification-based digital learning media; and (4) systemic challenges in implementing educational technology within Arabic language education contexts in Indonesia. Findings indicate a sharp increase in digital technology research following the COVID-19 pandemic (2020–2021), which catalyzed a paradigm shift from teacher-centered to student-centered, technology-mediated instruction. This review concludes that while digitalization presents significant opportunities for Arabic language education, persistent challenges, particularly educators' digital literacy gaps, unequal digital infrastructure, and a scarcity of contextually relevant Arabic digital content, must be addressed systemically to ensure equitable and effective learning outcomes.